RELIEF MEASURES OF ISLAMIC FINANCE IN COMBATING ADVERSE IMPACTS OF COVID 19 IN MALAYSIA: AN ANALYSIS - Syuhaeda Aeni Mat Ali; Azhani Arshad; Irini Ibrahim (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Coronavirus diseases or COVID-19 that initially started in Wuhan, China in 2019 had infected almost 80 million people around the globe. This outbreak has affected people in all aspects of life by forcing people to limit their normal daily life activities in order to combat the spread of the disease. Businesses are struggling to survive, unemployment arises but at the same time, people are obliged to pay expenses such as installments on their financings from financial institutions. Bank Negara Malaysia had introduced robust measures to soften the blow of the pandemic. During the Global Financial Crisis in 2008, Islamic finance has proven to be resilient and managed to survive the crisis without much substantial impact. However, the impact of COVID-19 is unprecedented and gives no exception to Islamic Finance. The purpose of this paper is to analyse the relief measures of Islamic finance in combating the adverse impacts of COVID-19 in Malaysia. The methodology adopted is doctrinal analysis. This is qualitative research. The research will be conducted to investigate the factual consequences and their effect on society. The significance of this study is to build greater resilience of Islamic Finance during this pandemic crisis, as well as in the post-COVID-19 environment. Findings disclose that Islamic finance faces liquidity issues, regulatory and digital challenges during this pandemic. Islamic finance must be value-driven and impact-focused to deliver Maqasid Shariah. Relief measures available include Financial technologies that enable Islamic Social finance instruments easily accessible during COVID-19 and Sukuk issuance to help micro-entrepreneurs and micro-businesses (SMEs). Shariah Advisory of Bank Negara Malaysia rulings on practices of restructuring documentation shows the flexibility of the Islamic Finance to adapt to the impact of post-Covid-19. Islamic finance should develop new jurisprudence under the preamble of Maqasid Shariah as a solution to overcome the impacts caused by COVID-19.